ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN MENGGUNAKAN METODE PERFORMANCE PRISM - Cahyawati, Amanda Nur; Pratikto, Pratikto; Soenoko, Rudy (JEMIS (Journal of Engineering & Management in Industrial System), 2013)
Good performance measurement is a measurement that covers all aspects of the stakeholders include investors, customer, employees, suppliers, regulators and communities. There is only one performance measurement that covers all aspects of stakeholders by using performance prism methods. Hospital X Malang is one example of an organization that use traditional performance measurement. Performance measurement has been done based on the financial side only, while the other aspects less noticed. Performance prism in this study aided by Analytical Hierarchy Process (AHP) and scoring system which includes objectives matrix and traffic light systems. The results was obtained 99 KPI consists of 17 investors, 35 customer, 16 employee, 15 supplier and 16 regulators and the community. Total index of the objective matrix is 7.9 and based on the traffic light system is in the yellow category.